ANALISIS KINERJA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA BERDASARKAN ECONOMIC VALUE ADDED DAN RETURN ON ASSETS - Bambang Widarno, Sophia Maranatha Hutapea, Rispantyo & (Universitas Slamet Riyadi, 2017)
Assessment of the performance of a company is a stage of job evaluation thatcan improve the quality of work. Every company has a quality standard to measurethe success of the company's performance. Similarly, four (4) cigarette sub-sectormanufacturing companies went public listed on the Stock Exchange that is PTGudang Garam, Tbk (GGRM), PT Hanjaya Mandala Sampoerna, Tbk (HMSP), PTBentoel International Investama, Tbk (RMBA), PT Wismilak Inti Mamur, Tbk(WIIM). The method used in this research is descriptive with quantitative approach,because it only describes the company's financial condition through quantitativecalculation Return On Asset (ROA) and Economic Value Added (EVA) concePT Thedata used in this study is secondary data. The results of this study indicate thataccording to the value of EVA WIIM is a company that has the best performancefrom 2013-2016 while for the value of ROA HMSP which has the best performance.In second order HMSP according to EVA and GGRM has good performanceaccording to ROA. In the third order based GGRM on the value of EVA and WIIMbased on ROA value. RMBA is a company that has a poor performance based on thevalue of EVA and ROA.Keywords: Company Performance, Economic Value Added, Return on Assets.